Penguatan Ketarbiyahan dan Keguruan di Lembaga Pendidikan Islam - Muhartini Muhartini; Amril Amril (Lembaga Pengembangan Kinerja Dosen, 2023)
The global era with the rapid and great advancement of information system technology, challenges teachers to have the ability to adapt themselves by improving scientific abilities and cutting-edge skills. But the most important thing is the ability to nurture students by sticking to sharia 'and can make them as noble ethical people. Efforts to strengthen tarbiyah and teacher training in Islamic educational institutions must make maximum efforts so that digital technology tools do not lull and deprive students of the right to get full control of teachers. This is the main mission of Islamic educational institutions so that the development of intelligent ethical humans can be reached by Islamic educational institutions. The three strategies that researchers offer in an effort to strengthen the conception of tarbiyah and teacher training in him and apply it to teacher professional performance activities are: (1) Understand and realize the achievement of tarbiyah and teacher goals; (2) Understand and apply the types of education and teaching; (3) Development of teacher soft skills so that they can become role models for students.